Implementation of the Viscometer Practicum Tool to Improve Conceptual Understanding of and Process Skills of Prospective Physics Teachers - Ruth Novi Kornalia Mellu; Infianto Boimau (Universitas Muhammadiyah Makassar, 2020)
A research have been done in order to implement viscometer learning media as an effort to improve students’ understanding towards the concepts and skill process in science for students in university who become the physic teachers candidate. This study used pre-experimental method through 0ne group pre-test-post-test design. The samples of this study were 30 students who were taking Fluid course. The techniques used to gain the data were test, questionnaires, observation by taking the students test questions, questionnaires sheets and observation sheets. The techniques used to analyze the data were double t-test, N-gain test and descriptive analysis in percentage by using Likert Scale. The result of data analysis using t-test showed that there was improvement on students’ comprehension towards science concepts and skill process that were taught using viscometer learning media. N-gain significance test also showed that there was an improvement on students’ comprehension in “medium” level by showing 0. 56 grade and students’ skill process was in ‘high’ category or 0.71 in grade. This means that the understanding of concepts and science skills of student’s increased significantly after being taught using a viscometer learning media. The result of observation sheets analysis showed that there was science skill process improvement by the average percentage was 85. 92%. Students responses were very positive towards the application of the using viscometer learning media in learning with 80,6% presentation. By therefore, using viscometer learning media implemented in learning can improve understanding of concepts and science process skills